Pharmacophore-based virtual screening of commercial databases against β-secretase 1 for drug development against Alzheimer’s disease - Han, Xu; Guo, Kaibo (Frontiers in Chemistry, 2024)
One of the most important proteins, β-secretase 1 is an aspartate protease. This membrane-associated protein is used for treating Alzheimer's disease (AD). Several inhibitors have been pursued against β-secretase 1 but still have not resulted effectively. Virtual screening based on pharmacophore has shown to be useful for lead optimisation and hit identification in the preliminary phase of developing a new drug. Here, we screen the commercially available databases to find the hits against -secretase 1 for the drug discovery against AD. The screening virtually for 200,000 compounds was done using a database of the VITAS-M Lab. Phase screen score was utilised to assess the screened hits. Molecular docking was performed in compounds having phase scores > 1.9. According to the study, the 66H ligand of the crystal structure has the maximum performance against the -secretase 1. The redocking of the co-crystal ligand showed that the docked ligand was seamlessly united with the crystal structure. The reference complex had three hydrogen bonds with Asp93, Asp289, and Gly291, one van der Waals interaction with Gly74, and three hydrophobic interactions. After equilibration, the RMSD of the reference compound sustained a value of ~ 1.5 Å till 30 ns and then boosted to 2.5 Å. On comparison, the RMSD of S1-complex steadily increased to ~2.5 Å at 15 ns, then displayed slight aberrations around ~ 2.5-3 Å till 80 ns, and then achieved steadiness towards the end of the simulation. The arrangements of proteins stayed condensed during mockup when bonded to these complexes, as stable Rg values showed. Furthermore, the MM/GBSA technique was employed to analyse both compounds' total binding free energy (ΔGtotal). Our research study provides a new understanding of using 66H as anti -secretase 1 for drug development against AD.